Factors influencing customer satisfaction and loyalty towards urban railway services in Hanoi: Mediating role of perceived value - Xuan Can Vuong; Thi Minh Trang Vu; Duc Anh Trieu; Trong Thuat Vu (PLoS ONE, 2026)
Understanding the satisfaction and loyalty of customers using urban railway services is important because customer loyalty is considered a key determinant of the operational and economic efficiency of this service. The purpose of this study is to explore the relationships between customer satisfaction and loyalty and their influencing factors, including service quality and perceived value. By using data collected from customers of Hanoi’s urban railways, a newly operating public transport system in Vietnam, this study uses confirmatory factor analysis (CFA) and structural equation modeling (SEM) to analyze the structural paths of the conceptual model. The results reveal that relationships are statistically significant and perceived value is an important mediator. The study concludes by drawing out implications that will help service providers, regulators, policymakers, planners, and researchers develop effective strategies to increase the use of urban railway services in Hanoi and other major cities.